SINTESIS DAN AKTIVITAS ANTIKANKER SENYAWA C-4-ALILOKSI-3-METOKSIFENILKALIKS[4]RESORSINARENA - Endah Sayekti; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa (Tanjungpura University, 2020)
The aims of this study was to synthesize of C-4-alyloxy-3-methoxyphenylcalix[4]resorcinarene (3). The syntheses was conducted by condensation reaction of resorcinol with 4-allyloxy-3-methoxybenzaldehyde (2) in ethanol with hydrochloric acid as a catalyst. The (2) compound was synthesized by the reaction of the 4-hydroxy-3-methoxybenzaldehyde (vanillin) (1) via allylation reaction using an allylbromide with the sodium metal as a catalyst in ethanol. A (3) compound was orange solid. m.p. of 176–177 °C (dec.). Yield (78%). FTIR (KBr, ν; cm-1): 3441 (-OH); 3086 and 3008 (Csp2-H); 2939 (Csp3-H ); 1612 (C=C aliphatic); 1512 (C=C aromatic); 1427 (>CH- methine); 1234, 1211, 1080 and 1018 (C-O-C asymmetric); 925 (C=CH2 terminal). 1H-NMR (DMSO-d6; 500 MHz) δ (ppm): 8,50 (8H, s, OH); 6.43 (4H, s, ArC-H); 6,36-6,38 (4H, d, J=10 Hz); 6.32 (4H, s, ArC-H); 6.26-6.28 (4H, d, J=10 Hz); 6.13 (4H, s, ArC-H); 6.00-6.05 (4H, m, =C-H); 5.38-5.40 (4H, d, J=10 Hz); 5.31 (4H, s, >C-H methine); 5.16-5.18 (4H, d, J=10 Hz); 4.34-4.36 (8H, d, J=10 Hz); 3.29 (12H, s, -OCH3). 13C-NMR (DMSO-d6; 500 MHz) dC (ppm): 33 (4 x CH methine); 55 (4 x CH3); 69 (4 x CH2-); 101 (4 x ArC-H); 112 (4 x ArC-H); 113 (4 x ArC-H); 116 (4 x =CH allyl terminal); 120 (4 x ArC-H); 122 (8x ArC-); 132 (4 x ArC-H); 134 (4 x =CH allyl); 137 (4 x ArC-); 145 (4 x ArC-O); 148 (4 x ArC-O); 152 (8 x ArC-OH). MS (ESI) m/z: 1137.5 (M+). Anticancer evaluation was performed on (3) compound by MTT (3-(4,5-dimethyltiazole-2-yl)-2,5-diphenyltetrazolium bromide) method showed that (3) compound has a cytotoxic activity against HeLa and T47D cells which IC50 value respectively are 13,58 and 65,26 µg/mL.